Prostate bed and organ-at-risk deformation: Prospective volumetric and dosimetric data from a phase II trial of stereotactic body radiotherapy after radical prostatectomy. (July 2020) - Yoon, Stephanie; Cao, Minsong; Aghdam, Nima; Shabsovich, David; Kahlon, Sartajdeep; Ballas, Leslie; Collins, Sean; Steinberg, Michael Lee; Kishan, Amar U.
Highlights: Stabilizing organ-at-risk anatomy (OAR) is essential. Interfraction prostate bed volume is stable despite deformable surrounding organs. Target underdosing and OAR overdosing is avoided in post-prostatectomy radiotherapy. Volumetric and dosimetric changes from rotation and intrafraction motion are minor. Shape of prostate bed may also influence target coverage. Abstract: Purpose: Stereotactic body radiotherapy (SBRT) in the post-prostatectomy setting is investigational. A major concern is the deformable prostate bed clinical target volume (CTV) and the closely juxtaposed organs-at-risk (OARs). We report a volumetric and dosimetric analysis of kilovoltage cone-beam CT (CBCT) data from the first 18 patients enrolled on a phase II trial of post-prostatectomy SBRT. With instructions on bladder filling and rectal preparation, we hypothesized acceptable CTV coverage while minimal overdosing to OARs could be achieved. Methods: All patients received 5 fractions of 6–6.8 Gy to the prostate bed. CBCT were taken prior to and halfway through each fraction. CTV and OARs were contoured for each CBCT. Changes in inter- and intra-fraction volume and dose were calculated. Relative changes in CTV V95%, bladder V32.5 Gy, and rectal V32.5 Gy and V27.5 Gy were evaluated. Results: Interfraction CTV volume remained stable, with median change +5.69% (IQR −1.73% to +9.84%). CTV V95% exhibited median change −0.74% (IQR −9.15% to −0.07%). Volumetric and dosimetric changes were minor from interfraction rotation and intrafraction motion. CTV V95% was ≥93% in 13 of 18 (72%) patients; in the remaining five, median change was −14.09% (IQR −16.64% to −13.56%). Interfraction CTV volume change was significantly larger among patients with CTV V95% <93% (+25.04% vs. +2.85%, p  = 0.002). Conclusions: With specific bladder and rectum filling protocols, CTV underdosing and overdosing to bladder and rectum are avoided in majority of patients. Changes in CTV shape may account for the underdosing that may be observed.